Evaluation of different bonding strategies for glass fibre-reinforced epoxy resin with embedded elastomer layers. (14th September 2022) - Semar, Jan Eric; May, David; Mitschang, Peter
ABSTRACT: Embedding elastomer layers in fibre reinforced polymer composites can be used to improve their performance. In this work, the creation of such composites via resin transfer moulding has been experimentally investigated with a focus on bonding between elastomer and composite layers. Different process variants were used and tests similar to ISO 6922 were performed to determine bonding strength. Bonding strengths were similar for most process variants (4–5 MPa), but differences in failure mode were observed. When the elastomer was vulcanised before injection (co-bonding), the specimens failed adhesively but microsections show a homogenous material. When injection was done prior or simultaneously (co-curing) to vulcanisation, cohesive or combined failure could be achieved but microsections reveal pores in the elastomer. This makes co-curing promising for structural applications but further research is necessary to achieve a flawless material. Co-bonding is a simpler process but adhesive failure is undesirable. However, it might be suitable for non-structural parts.